Trusted computing and information security : 11th Chinese Conference, CTCIS 2017, Changsha, China, September 14-17, 2017, Proceedings /: 11th Chinese Conference, CTCIS 2017, Changsha, China, September 14-17, 2017, Proceedings. (2017) - Unknown
No abstract available